If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -10x + -7(5 + -2x) = -7 -10x + (5 * -7 + -2x * -7) = -7 -10x + (-35 + 14x) = -7 Reorder the terms: -35 + -10x + 14x = -7 Combine like terms: -10x + 14x = 4x -35 + 4x = -7 Solving -35 + 4x = -7 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '35' to each side of the equation. -35 + 35 + 4x = -7 + 35 Combine like terms: -35 + 35 = 0 0 + 4x = -7 + 35 4x = -7 + 35 Combine like terms: -7 + 35 = 28 4x = 28 Divide each side by '4'. x = 7 Simplifying x = 7
| 351+x=374 | | 98=6.5x+20 | | 4+4(x-5)=-2 | | 4.75x+25=22.5625+5x | | 14x+7=35 | | 2-2(n+4)=4 | | 25*x=x*5 | | X-5a=b | | 250*3.62= | | -3+2=-10+3y | | 80/4=5/w | | 3x+4(x+3)=19 | | 4=6.5x+20 | | 33/-19 | | 2.1n=1.16666667 | | 2-2x=2x-19 | | 3s+3s-5s=7 | | 2w+4l=3a | | 18q+2q-15q+3q=8 | | 2-8x=2-9x | | 33/33 | | -(-6y-13)-15y+(7y-16)=-26 | | 4/x=8/20 | | 13/16=x/100 | | 10x-5=-25 | | 5x-38=46x+6 | | -6+3y=-18 | | 15x-11x+3x=7 | | Z-7/9=z/9 | | 6c+c-5c+2c-2c=20 | | x^2-2(2.8)x-6=0 | | -3x+5x+2=28 |